Doorway of the sanctum - Temples of India Project Team (Jio Institute, 2024)
The lintel of the sanctum-doorway shows a two-armed depiction of Lakulisha seated in padmasana in dhyanmudra, carrying a lakuta, or club, in his left hand and a fruit in his right hand—part of his standard iconography—inside a niche on the lalatabimba. On either side of the lintel is a four-armed depiction of Brahma on the left and of Vishnu on the right. Replacement of the image of Shiva with Lakulisha at the lintel niches of the sanctum doorway was once a common feature of the Pashupata tradition.